Micro/macro-stress relationship and local stress distribution in polyethylene spherulites upon uniaxial stretching in the small strain domain. (28th March 2018) - Xiong, Bijin; Lame, Olivier; Seguela, Roland; Men, Yongfeng
Abstract: Local stress of polyethylene spherulites under uniaxial stretching in small strain domain has been investigated by in-situ wide angle X-ray diffraction (WAXD) in comparison with macroscopic stress. Particular attention is paid to the elastic strain range. The local stress in equatorial and polar regions both increase in absolute value and follow a linear relation versus macroscopic stress. However, local stress turns out to be heterogeneous over the whole spherulites volume. The polar region shows higher local stress than equatorial region. Moreover, local stress along the a and b crystallographic axes in the crystalline lamellae enable determining the local stress triaxiality which is heterogenous. The increase of crystallinity promotes stress distribution heterogeneity throughout the spherulites. The origin of these phenomenon are discussed in terms of crystalline network percolation and effect of amorphous layer that modifies the local mechanical behavior. The present study provides a useful means for achieving the scale transition between the micro and the macro structural levels that is necessary for the modeling of the mechanical behavior of semi-crystalline polymers via micromechanical approaches. Graphical abstract: Highlights: Local stress in spherulites of polyethylene has been measured. A method for local stress measurement via in-situ WAXD is proposed. Micro/macro-stress relationship has been revealed.